2021
DOI: 10.1097/md.0000000000026383
|View full text |Cite
|
Sign up to set email alerts
|

Sphenoid sinus pseudoaneurysm with carotid cavernous fistula presenting with delayed subarachnoid hemorrhage

Abstract: Rationale: Sphenoid sinus pseudoaneurysm arising from the cavernous segment of the internal carotid artery (ICA) caused by traumatic vessel injury is rare, and rarer is a concomitant carotid-cavernous fistula (CCF). In particular, delayed subarachnoid hemorrhage (SAH) due to pseudoaneurysm rupture has not been reported to-date in literature. Here, we report a case of sphenoid sinus pseudoaneurysm with CCF presenting with delayed SAH. Patient concerns: A 73-year-old man … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…is entity may present either massive epistaxis, a life-threatening clinical situation, or ophthalmic symptoms of venous engorgement, including proptosis, chemosis, bruit, and vision impairment. [5,24] Early recognition is essential to prevent the development of severe massive hemorrhage from epistaxis. [30] Fortunately, we recognized sphenoid sinus pseudoaneurysm in our case 2 and 3 before the development of massive epistaxis.…”
Section: Concomitant Tccf and Pseudoaneurysm Within The Sphenoid Sinusmentioning
confidence: 99%
See 1 more Smart Citation
“…is entity may present either massive epistaxis, a life-threatening clinical situation, or ophthalmic symptoms of venous engorgement, including proptosis, chemosis, bruit, and vision impairment. [5,24] Early recognition is essential to prevent the development of severe massive hemorrhage from epistaxis. [30] Fortunately, we recognized sphenoid sinus pseudoaneurysm in our case 2 and 3 before the development of massive epistaxis.…”
Section: Concomitant Tccf and Pseudoaneurysm Within The Sphenoid Sinusmentioning
confidence: 99%
“…Recently, Cho et al [5] demonstrated successful treatment of TCCF accompanied by a giant pseudoaneurysm in the sphenoid sinus by endovascular treatment with intra-arterial approach using multiple coils and an ethylene-vinyl alcohol (EVOH) copolymer-based liquid embolic agent injection while protecting the injured site of the ICA with a balloon catheter. However, this technique required much higher cost than our technique.…”
Section: Concomitant Tccf and Pseudoaneurysm Within The Sphenoid Sinusmentioning
confidence: 99%